The early relationship of mother and pre-infant: Merleau-Ponty and pregnancy - Wynn, Francine (Nursing philosophy, 2002)
This paper critically evaluates current conceptions of pregnancy as a possession of either mother or infant. In opposition to the more common stance that marks birth as the beginning of intercorporeality and perception, pregnancy is instead phenomenologically delineated as a chiasmic relationship between mother and her pre-infant from a Merleau-Pontian perspective. This paper maintains that during pregnancy a mother-to-be and her pre-infant are deepened and modified through their intertwining.